Analisis Program Magang Internasional Terhadap Pengembangan Kompetensi Manajerial Mahasiswa Program Studi Manajemen Bisnis Syariah UMSU - Diaz Muhammad Fahrel; Hayati Isra (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The international internship program is one of the efforts to improve student competency, especially in managerial aspects that are relevant to the world of work. This study aims to analyze the impact of the implementation of the International Internship Program on the development of managerial competency of students of the Sharia Business Management Study Program, Muhammadiyah University of North Sumatra (UMSU). This program was implemented at the Al-Qudwah Integration Islamic Elementary School, Selangor, Malaysia, from August 6 to August 27, 2024. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results of the study showed that this internship program provided practical experience for students in various managerial aspects, such as school administration management, financial records, and student and teacher attendance management systems. In addition, students also face various challenges, such as adaptation to work culture and language, lack of written guidelines in administration, and difficulties in adjusting to a new work environment. However, these challenges can be overcome through active communication with school staff, guidance from internship instructors, and further understanding of the applicable work system. The conclusion of this study is that the International Internship Program contributes significantly to developing students' managerial competencies, especially in the aspects of administrative management, professional communication, problem solving, and adaptation in an international work environment.